Mapping Age Of Oil Palm Trees Using Google Earth Engine Cloud Computing In Pt. Scp, Pulang Pisau Regency - Putra, Akbar Cahyadhi Pratama; Widhaningtyas, Tantri Utami; Fariz, Trida Ridho; Prakoso, Aji (Jurusan Budidaya Perkebunan, 2023)
The aim of this research is to utilize remote sensing data and use the GEE platform to detect the age of oil palms using Landsat 8 OLI data at the Sebangau Kuala Plantation in Pulang Pisau Regency, Central Kalimantan. This research was analyzed using the Google Earth Engine using FCD (Forest Canopy Density) analysis. The results of the model correlation with the conditions of the year of planting in the field through ARESTA (area statement) are 0.63 or have a strong relationship. The RMSE (Root Mean Square Error) value of the FCD (Forest Canopy Density) model is 0.661, which means that the error value is small and can be used as a model reference. The use of remote sensing and GEE makes the process of mapping the age of oil palm more effective. The results of the research show that mapping the age of oil palm using GEE is very efficient based on computing time, so it is very suitable for use in oil palm plantations.